Preferences for redistribution in the US, Italy, Norway: An experiment study - Gianluca Grimalda; Francesco Farina; Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2018)
We examine experimentally individual preferences for redistributions in the US, Italy, and Norway. Twenty-one subjects were assigned initial earnings from a discrete uniform distribution. The source of earnings was manipulated and depended either on luck or on individual relative performance in some tasks. All subjects chose a redistribution rate to be applied to group members' earnings. One choice was then randomly selected to determine final earnings. Four different experimental decisions altered whether subjects' choice applied only to others, thus making self-interest irrelevant (impartial decision), and the degree of information over one's earnings. Norwegian subjects demanded significantly higher levels of redistribution both in the impartial decision and when self-interest offered the most clear-cut prescription, as uncertainty over one's earnings was removed. The demands for redistributions by US and Italian participants were instead similar. Conversely, country differences disappeared in decisions where earnings were uncertain. Contrary to widely held views, no evidence was found that US subjects were more "meritocratic" than others. Italian subjects reacted the most to the source of inequality, decreasing demand for redistribution in Performance treatments compared to Luck treatments. While behaviour of subjects whose earnings were above the median level (the "rich") did not differ significantly across countries, large differences emerged for people below the median level (the "poor") in the fourth decision. Italian "poor" were agreeable to let the "rich" receive a large share of their earnings, particularly so in Performance treatments. Conversely, Norwegians "poor" demanded full earnings equalisation. The behaviour of US subjects fell between these two extremes. This evidence shows the existence of relevant cross-country difference in demand for redistribution and opens new perspectives on what may be considered "fair" or "unfair" inequality in Western countries.
Keywords: D63; D71; C92; 330; inequality; Redistribution; individual merit; cross-country experiments